2013
DOI: 10.1002/0471142905.hg0123s76
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Admixture Mapping

Abstract: Admixture mapping is a powerful method of gene mapping for diseases or traits that show differential risk by ancestry. Admixture mapping has been applied most often to African Americans who trace ancestry to Europeans and West Africans. Recent developments in admixture mapping include improvements in methods to take advantage of higher densities of genetic variants as well as extensions to admixed populations with three or more ancestral populations, such as Latino Americans. In this unit, I outline the key co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 19 publications
0
64
0
2
Order By: Relevance
“…This approach uses admixture information to localize disease-associated polymorphisms that are divergent in frequency in the parental populations that have contributed to the population under study. MALD assumes that the genomic region containing disease-susceptibility alleles will be enriched for ancestry from the parental population in which disease risk is more prevalent [111]. Thus, MALD can be used to identify regions of the genome that potentially contain loci associated with differential disease susceptibility.…”
Section: Implications Of Genetic Structure and Admixture For Disease mentioning
confidence: 99%
“…This approach uses admixture information to localize disease-associated polymorphisms that are divergent in frequency in the parental populations that have contributed to the population under study. MALD assumes that the genomic region containing disease-susceptibility alleles will be enriched for ancestry from the parental population in which disease risk is more prevalent [111]. Thus, MALD can be used to identify regions of the genome that potentially contain loci associated with differential disease susceptibility.…”
Section: Implications Of Genetic Structure and Admixture For Disease mentioning
confidence: 99%
“…There are several software programs available for ancestry estimation; however, it has been suggested that LAMP-LD is currently the most accurate software available to estimate local ancestry inference among unrelated individuals. 40,73 This provides higher resolution for ancestry switches and allows detection of smaller local ancestry regions. We acknowledge that despite the availability of a dense set of markers, we were limited by the use of a predefined set of GWAS SNPs and the subsequent loss during quality control.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore impera ve to penalize SNPs that are correlated with popula on structure, as the lack of controlled experiments can generate spurious associa ons between gene c variants more common in some human ancestry groups with regional measurement errors or different cultural and nutri onal environments 56 . When a popula on includes mul ple ancestries with different disease suscep bili es, popula on structure correc on can obscure real signals, which has in turn led to the development of admixture mapping 57 . Similarly, in animal or plant breeding, SNPs conferring an advantageous trait but that are highly associated with a par cular group of breeds or varie es (the equivalent of geographic popula ons) are also avoided, as selec on of these SNPs can drag along undesirable traits from such parents 58 .…”
Section: V3 Important Notes On Popula On Structure Correc On In a Wimentioning
confidence: 99%